TINDAK UJAR KONFLIKTIF DALAM NOVEL MURDER IN THE MEWS KARYA AGATHA CHRISTIE (SUATU ANALISIS PRAGMATIK) - Husain, Dedi Iskandar; Jansen, Frieda Th.; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â This study entitled â€œConflictive Act in the Novel Murder in The Mews by Agatha Christieâ€. It is an analysis of Pragmatic investigation that focus on one aspect of speech acts called Illocutionary act. It is attempt to find the kinds and Function of Illocutionary act in the Novel. The data have been taken from characters utterancesâ€™ in the Novel. The writer analyzed the data descriptively by concentrating on utterances which contain Illocution. The theory use in this research is taken from Leechâ€™s theory about illocutionarry actsâ€™ classification. The finding of this research show that the kinds of function of the illocutionary act are found in the Novel â€œMurder in the Mewsâ€.It is classified into four categories, those are threatening, reprimanding, accusing, and cursing. Theoretically the writer extends that this research can give any contribution for students or readers to understands kinds of illocutionary act and their functions are not only in this novel, but also in the literary works especially in daily conversation/communication.Â Â Â Â Â Keywords: Illocutionary, Nove, Pragmatics Analysis